2005
DOI: 10.5713/ajas.2005.85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Green Tea Polyphenols and Fructo-oligosaccharides in Semi-purified Diets on Broilers` Performance and Caecal Microflora and Their Metabolites

Abstract: This study was conducted to examine the effects of green tea polyphenols (GTP) and fructo-oligosaccharides (FOS) supplement on performance, counts of caecal microflora and its metabolites production. In female broiler chickens fed on semi-purified diets from 28 to 42 d of age, dietary green tea polyphenols (GTP) and fructo-oligosaccharides (FOS) significantly reduced mortality (p<0.05). Dietary GTP significantly decreased the total count of caecal microflora, each colonic population count and caecal flora meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 27 publications
(27 reference statements)
4
41
0
3
Order By: Relevance
“…Other bioactive components reported in green tea include tannins, caffeine, amino acids and vitamins (Tsuneki et al, 2004). From a number of animal studies, it has shown that the bioactive component of green tea improves bodyweight gain and feed efficiency in pigs (Sarker et al, 2010b;Hossain et al, 2012a), calves (Sarker et al, 2010a) and broilers (Cao et al, 2005). Horax et al (2002) reported that green tea extracts could reduce the thiobarbituric acid-reactive substance (TBARS) values in raw meats during storage.…”
Section: Introductionmentioning
confidence: 99%
“…Other bioactive components reported in green tea include tannins, caffeine, amino acids and vitamins (Tsuneki et al, 2004). From a number of animal studies, it has shown that the bioactive component of green tea improves bodyweight gain and feed efficiency in pigs (Sarker et al, 2010b;Hossain et al, 2012a), calves (Sarker et al, 2010a) and broilers (Cao et al, 2005). Horax et al (2002) reported that green tea extracts could reduce the thiobarbituric acid-reactive substance (TBARS) values in raw meats during storage.…”
Section: Introductionmentioning
confidence: 99%
“…and certain butyrate producing bacteria (Prestamo et al, 2003;Huang et al, 2012;Ramnani et al, 2012;Cardona et al, 2013;Fechner et al, 2013;Duenas et al, 2015). At the same time, they suppress the growth of toxogenic E. coli and proteolytic bacteria like Clostridium perfringens, Streptococcus sp., peptococci, bacilli, Staphylococcus sp., bacteriodaeceae, pseudomonad, yeast and mould (Samarasinghe et al, 2003;Cao et al, 2005;Rohin et al, 2014;Asian J. Anim. Vet.…”
Section: Microbiological Attributesmentioning
confidence: 99%
“…Green tea supplementation has been shown to improve body weight gain in broilers (Biswas and Wakita 2001) and pigs (Hossain et al 2012). The beneficial effects of GT by-products (Yang et al 2003;Cao et al 2005;), extract (Shomal et al 2012;Farahat et al 2016) and powder (Biswas and Wakita 2001;Alimohammadi-Saraee et al 2014) on performance and health of poultry have been reported. These effects of dietary green tea have been mainly attributed to its polyphenols (Ninomiya et al 1997;Gramza et al 2005;Khan 2014) which are reported to have antioxidant (Molan et al 2009;Sahin et al 2010) and antimicrobial (Jang et al 2007;Erener et al 2011;Khan 2014) activities.…”
Section: Introductionmentioning
confidence: 99%